Effects of using titanium dioxide nanoparticles in seed submersion and soil amendment on rice growth and yield - Theerak, Winakon; Ditthakit, Parichart; Puttamul, Thamrongjet (Agriculture and Natural Resources, 2024)
Importance of the work: Titanium dioxide nanoparticles (TNPs) can enhance rice production; however, few studies have systematically investigated the effects of both TNP size and concentration. Objectives: To determine the effects of TNPs in seed submersion and soil amendments on rice growth and yield. Materials and Methods: A two-factor completely randomized design was used. Suspensions of 23 nm, 104 nm and 486 nm diameter TNPs were prepared at concentrations of 0–1,000 mg/L. Pathum Thani 1 and Khao Dok Mali 105 (KDML105) rice seeds were submerged. The soil was amended with TNPs. Rice growth, rice yield and titanium accumulation were recorded. Results: TNP treatments promoted plant height, chlorophyll content, the number of tillers per plant, weight and the number of good-quality seeds. TNPs had no effect on yield quality. Larger TNPs at a higher concentration led to greater plant height and chlorophyll content in both cultivars. Smaller TNPs at higher concentrations led to greater titanium accumulation in rice. The improvement of rice growth by TNPs was due to the promotion of photosynthesis. Smaller TNPs could penetrate rice tissues more readily, causing greater bioaccumulation. Larger TNPs agglomerated less in water, entered cytoplasm more efficiently and thus promoted photosynthesis more effectively. However, improved photosynthesis alone would not be sufficient for enhancing yield and yield quality. Main finding: The combination of seed submersion and soil amendment with 486 nm TNPs at 1,000 mg/L concentration was recommended for improving rice growth. Future studies should explore the use of TNPs with other fertilizers to enhance rice yield and yield quality.